Fine Particulate Air Pollution and First Hospital Admissions for Ischemic Stroke in Beijing, China - Yaohua Tian; Xiao Xiang; Yiqun Wu; Yaying Cao; Jing Song; Kexin Sun; Hui Liu; Yonghua Hu (Scientific Reports, 2017)
Abstract The primary objective of this study was to assess the association between short-term changes in ambient fine particulate matter (PM2.5) and first hospital admissions for ischemic stroke. We identified 63,956 first hospital admissions for ischemic stroke from the Beijing Medical Claim Data for Employees from January 1, 2010, through June 30, 2012. A generalized additive Poisson model was applied to explore the association between PM2.5 and admissions for ischemic stroke. We also explore the effect modification of risk by age and gender. The exposure–response relationship between PM2.5 and admissions for ischemic stroke was approximately linear, with a relatively stable response at lower concentrations (<100 μg/m3) and a steeper response at higher concentrations. A 10 μg/m3 increase in the same-day PM2.5 concentration was associated with 0.31% (95% CI, 0.17–0.45%, P < 1.57 × 10−5) increase in the daily admissions for ischemic stroke. The association was also statistically significant at lag 1, 2, 3, 0–2 and 0–4 days. Subgroup analyses showed that the association was not different between patients ≥65 years and <65 years old or between males and females. In conclusion, short-term exposure to PM2.5 was positively associated with first hospital admissions for ischemic stroke in Beijing, China.